Arquitetura OTN Switch com funcionalidades de cross-conexão e multiplexação óptica e digital em Redes OTN - Dilem, Matheus Brunoro (2014)
The demand for new data transport technologies increasingly fast and with guarantees of QoS (Quality of Service), caused by Internet traffic growth, brings a great challenge in the area of telecommunications networks. The optical transport networks are presented as a solution to the high transmission rates. In order to make the Core Networks more flexible and adjusted to the dynamics and heterogeneity of demands, the ITU-T (International Telecommunication Union - Telecommunication Standardization Sector) develops a series of recommendations addressing the most diverse characteristics of OTN (Optical Transport Network) networks in the context of Networks Center, determining its functionality. This dissertation aims to develop a proposal of OTN Switch architecture with the operation of cross-connection and multiplexing of optical and digital signals present in the OTN networks. To this end, the arqchitecture is based in the recommendations generated by the ITU-T, making it capable of providing interoperability with existing equipment.